Embryo rescue and induction of somatic embryogenesis as a method to overcome seed inviability in Zea mays ssp. mays × Zea mays ssp. parviglumis crosses - García, Maria Dina (2001)
Zea mays ssp. mays (2n=40) and Z. mays ssp. parviglumis (2n=20) were crossed to obtain hybrid plants by embryo rescue. Hybrid embryos were isolated and cultured on Garcia et al. (1992) basic medium supplemented with 2,4-dichlorophenoxyacetic acid and/or kinetin in different concentrations. Caryopses harvested 23 d after pollination (DAP) were turgid, with 0.3 to 0.5 mm long embryos, while those harvested 30 DAP were shrunken, with 1 to 1.5 mm long embryos. Twenty days after plating, 100 % of the younger embryos gave rise to white, compact embryogenic calli. Subsequently, coleoptiles, leaf-like structures, shoots and roots originated from them and 35 hybrid plants were regenerated from 60 embryos. Embryogenic or organogenic calli frequencies did not differ among hormonal treatments, but they decreased, on average, from 90.5 to 44.3 %, comparing 50 and 120-d-old cultures. The older embryos regenerated plants only by germination, although they gave rise to organogenic callus with low frequencies. Regenerated plants showed a somatic chromosome number of 2n=30, pollen fertility of 40 to 80 % and 15 % viable naked caryopses.